Tobacco consumption among health science students of selected colleges in Kathmandu valley, Nepal. - Kapali,Sujana (2019)
ABSTRACT: ABSTRACT: Background: Tobacco products are products made entirely or partly of leaf tobacco as raw material, which are intended to be smoked, sucked, chewed or snuffed. Tobacco use is one of the main risk factors for a number of chronic diseases. Despite this, it is common throughout the world. Health professional students play a critical role in tobacco control by providing services, advocating for policies and serving as role models for social change. But, despite the knowledge, health science students are, themselves consuming tobacco products. Objectives: The overall objective is to find out the prevalence of the use of tobacco among health science students of Kathmandu. Methodology: A descriptive cross-sectional study design was used to conduct the study. Purposive sampling was adopted for college selection and simple random sampling was adopted for respondent selection. Self-administered questionnaire was used to collect the information from 216 respondents. The obtained data was coded, decoded where necessary, calculated, analyzed, tabulated and interpreted by using IBM SPSS 21 statistical tool. Results: The findings of the study shows that 51.4 percent of the respondents ever used and 44.1 percent among them still use tobacco products. Prevalence of tobacco consumption was 22.68 percent. Hukkah consumption was relatively higher than the use of other tobacco products. 64.9 percent of the respondents started using tobacco products due to curiosity. 37.8 percent of the students started using tobacco products at 18-19 years of age. 62.5 percent, i.e., majority of the students had good knowledge about the hazards of tobacco consumption, and yet, out of 44.1 percent respondents who used tobacco products, 44.9 percent had high use and 55.1 percent had low use of tobacco products. There was a strong association (p=0.000) between sex and use of tobacco, (p=0.001) between place of buying tobacco products and use of tobacco, distance of place of buying tobacco products (p=0.000) and use of tobacco, (p=0.046) between self-earning and use of tobacco. Conclusion: There is a substantial amount of tobacco use among the health science students themselves, despite having good knowledge about its hazards. Thus, frequent positive reinforcement of anti smoking campaign focusing more on youth and focus on tobacco prevention and cessation training/counseling in health science colleges would be desirable.